Evaluating the trophic ecology and feeding habits of three divergent lineages of Sandelia bainsii (Teleostei: Anabantidae), from the Eastern Cape Rivers using stable isotope analysis - Nkomo, Thulisile (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Despite supporting a disproportionately large fraction of the global biodiversity, freshwater ecosystems are ranked as the most highly threatened habitats on the planet, ahead of both terrestrial and marine ecosystems. Many regions are still characterised by limited knowledge regarding the taxonomy and ecology of freshwater fish taxa. The need for ecological information is increasingly becoming important due to the discovery of new species and unique lineages, which require conservation management. The aim of this study was thus to evaluate the trophic ecology and feeding habits of the three recently described and divergent Sandelia bainsii lineages, namely Sandelia sp. 'bainsii Kowie' from the Great Fish River, Sandelia sp. 'bainsii Keiskamma' found in the Keiskamma River, and Sandelia sp. 'bainsii Buffalo' confined to the Buffalo River system in the Amathole-Winterberg freshwater ecoregion in the Eastern Cape Province, South Africa. Based on the allopatric distribution and the generalist feeding habits of these lineages, this thesis postulated that these three lineages were likely to show similar trophic ecology patterns, different dietary composition and as a result would have variable trophic positioning in the different river systems. Therefore, the primary objectives were to use stable isotope analysis to (1) evaluate the food web patterns of the river systems where the three S. bainsii lineages occurred, and (2) determine dietary source contributions for the three lineages using isotope mixing models. The results revealed general variability and significant differences in the Î´13C and Î´Â¹â µN values for the different basal resources, macroinvertebrates and fish community across the different headwater streams. Within and across the different rivers, the S. bainsii lineages exhibited variable isotopic niche sizes, which appeared to coincide with the variation in the isotopic composition of the individual communities. Furthermore, these lineages did not exhibit any discernible patterns in their interspecific interactions in different habitats. This suggests that these lineages' isotopic niche patterns were largely influenced by spatial differences in both trophic resources and probable interactions with contraspecifics. Assessment of trophic positions of S. bainsii lineages showed that the three lineages had higher trophic positions than other co-occurring species at most sites, except in the Buffalo River. This suggest that the different lineages were generally top predators in the different river systems. Although S. 'bainsii Buffalo' had a lower trophic position compared to other co-occurring species, its trophic position was generally characterised by high uncertainty, indicating that this lineage was likely influenced by the occurrence of diet sources that had highly variable stable isotope values. Findings from stable isotope mixing models revealed that the diet sources varied from the dominance of either single diet source in the Fairburn and Tyume 1 River to the importance of multiple prey sources from the Lushington and Kat River system. This suggests that despite being a top predator at most sites, the diet sources for the different lineages were highly variable. The patterns observed in this study did not appear to be attributed to species divergence possibly caused by allopatric speciation, but rather differences in food web characteristics of the river systems, as well as the lineages interspecific relationships and their generalized feeding strategies. Understanding the trophic dynamics of these lineages will assist in implementing effective conservation strategies and policies dealing with narrowly distributed species that are threatened by habitat fragmentation and invasion of piscivorous fish.
Keywords: Anabantidae; Trophic ecology; Food chains (Ecology); Food web; Freshwater fishes Food; Stable isotopes